Effect of Two Pepper Powders (Piper nigrum and Piper guineense) as A Feed Additive in The Ration on Intake and In vivo Digestibility in Cavies (Cavia porcellus L.) - MBOGNOU SESSON Nathalie; MIEGOUE Emile; NOUMBISSI Marie Noëlle Bertine; FOKOM WAUFFO David; KWAYEP NYAH Cédric; KENNE NOUBOUSSI Christèle; DJOUMESSI TOBOU France-Gina; MATHO Amandine; DEFANG Fuelefac Henry (Universitas Airlangga, 2023)
Background: Cavies are an essential element in a rural landscape in some African countries as food resources or income sources. Purpose: To study the effects of two peppers (Piper nigrum and Piper guineense) as a feed additive in ration on feed intake and In vivo digestibility of nutrients in cavies in order to improve their productivity. Methods: The experiment consisted of a completely random design of four groups of 5 males and five females per group (40 cavies with weights of 450±50g). The control diet was given to group 1 animals (T0) containing no pepper. The cavies in groups 2 (T1), 3 (T2), and 4 (T3) were fed 0.5% Piper nigrum powder, 0.5% Piper guineense powder, and 0.25% Piper nigrum powder + 0.25% Piper guineense powder, respectively. Similarly, Trypsacum laxum grass was weighed before being served. Results: The study showed that although not significantly (p>0.05), Dry matter (DM), Organic Matter (OM), crude protein (CP), and crude fiber (CF) were higher in animals fed the T0 control ratio compared to the other groups (37.94 g DM/d/animal; 33.71 g DM/d/animal; 5.28 g DM/d/animal and 6.45 g DM/d/animal respectively). In addition, the incorporation of the two peppers (Piper nigrum and Piper guineense) as a feed additive in the ration non-significantly (p>0.05) increased the apparent digestive utilization coefficients (aDUC) of food constituents (DM, OM, CP, and CF) in the cavies. Conclusion: Based on these results, the use of pepper powder in the ration can be considered at an incorporation rate of 0.5% for good feed intake and up to 0.5% for better digestive utilization of nutrients in guinea pigs. The use of a synergy (0.25% of Piper nigrum + 0.25% of Piper guineense) can be considered.